The Effect of Instagram Reels on Arabic Vocabulary Learning Outcomes - Fadila Khairunisa; Muhammad Tolal Kaema; Barihan Ibrahim (Journal of Arabic Literature, Teaching and Learning, 2025)
As one of the important elements in language, vocabulary learning should be a priority in language learning, especially Arabic. However, in reality there are still many students who have not mastered the Arabic vocabulary taught and the lack of media utilization used by teachers in learning Arabic vocabulary. This study aims to determine the effect of Instagram Reels media on Arabic vocabulary learning outcomes. This research used pre-experimental method with one group pretest posttest design through quantitative approach. The instrument in this study consisted of Arabic vocabulary written test in the form of pretest and posttest. The results of this study indicate that there is an increase in the learning value of students' Arabic vocabulary as evidenced by the paired t-test with a significance level (sig) two-sided p 0.001 <0.05 so that Ha is accepted and H0 is rejected. The implication of this study shows that the use of Instagram reels is proven effective in improving the mastery of Arabic vocabulary, because it presents the material visually and interestingly. The creative short video content facilitates understanding and strengthens the learner's memory of new vocabulary. with that Instagram reels can be used as an innovative and fun alternative learning media in the Arabic language learning process.